Teste e análise de um dispositivo de calibração para anemometria de fio quente - Pereira, Marvin [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The present work intends to validate a device for hot film anemometry calibration. The device was built to generate an asymmetric free water jet, which volumetric flux can be monitored by a rotameter connected to the system. Knowing the analytical speed profile and the diameter of the asymmetric free jet, it is possible to determine the speed at the center of the jet. In this way, it is possible to construct the calibration curve, by recording the anemometer tension measurements for the respective speed measurements. During the tests, some instability problems were identified and minimized, however, they have not been completely eliminated. The main hypothesis for the cause of the problem is related to probe contamination in the device. The observed instability levels imply a certain difficulty to carry out the calibration, however, they do not render the device useless, which allows a satisfactory calibration to be performed, provided that certain precautions are taken.

O presente trabalho pretende validar um dispositivo para calibração de anemometria de fio quente. O dispositivo foi construído para gerar um jato de água livre axissimétrico, cujo vazão pode ser monitorada por um rotâmetro conectado ao sistema. Conhecendo-se o perfil de velocidade analítico e o diâmetro do jato livre assimétrico, pode-se determinar a velocidade no centro do jato. Desta forma, registrando as medidas de tensão do anemômetro para as respectivas medidas de velocidade, é possível construir a curva de calibração. No decorrer dos ensaios, alguns problemas de estabilidade foram identificados e minimizados, entretanto, não foram completamente eliminados. A principal hipótese para a causa do problema está relacionada à fácil contaminação da sonda no dispositivo. Os níveis de instabilidade observados implicam em uma certa dificuldade para realizar a calibração, entretanto, não inutilizam o dispositivo, que permite realizar uma calibração satisfatória desde de que certos cuidados sejam tomados.
Test and analysis of a calibration device for hot-wire anemometry
Keywords: Hot wire anemometer; Calibration device; Axisymmetric free jet; Anemômetro de fio quente; Dispositivo de Calibração; Jato livre axissimétrico